Pengaruh Unit Pelayanan, Jenis Kelamin Dan Metode Pembayaran Terhadap Kepuasan Pasien Rumah Sakit: The Influence of Service Unit, Gender and Payment Method on Hospital Patient Satisfaction - Febriyani, Renny (Dohara POAJ, 2025)
Introduction: Patient satisfaction can be interpreted as one part of the quality of service that directly or indirectly affects hospital services. Patient satisfaction can be felt by someone who has seen results (outcomes) that meet their expectations. The purpose of this study was to determine the effect of service units, gender and payment methods on patient satisfaction at Hospital X Cileungsi in December 2022 - January 2023. Methods: The quantitative research method uses an analytic observational method with a cross sectional study design. The research data use data driven research with the data source used namely secondary data obtained from the results of questionnaires obtained from hospital records in the quality and accreditation section. The sampling technique uses the Non Probability Sampling technique by means of Purposive Sampling. The study population was all patients of Hospital X Cileungsi who received emergency ward, outpatient and inpatient care with inclusion criteria of 1208 respondents. Results: Based on the research results, it is known that there is an influence of service unit (sig < 0,001) gender (sig < 0,002) and method of payment (sig < 0,001) on patient satisfaction. Discussion: It is hoped that the results of this study can be input so that the managerial division of the hospital is to be able to evaluate the service standards provided to patients in outpatient and inpatient care so that patients do not only feel satisfied in the emergency ward but can also feel satisfied with outpatient and inpatient services.